The (In)visibility of Groomed Ski Runs. (April 2019) - Harrison, William J.
I analyse the visibility of "groomed" ski runs under different lighting conditions. A model of human contrast sensitivity predicts that the spatial period of groomed snow may render it invisible in the shade or on overcast days. I confirm this prediction with visual demonstrations and make a suggestion to improve visibility.